Safety boots - Peh, Hoo Keong; Abubakar, Muhammad Umarazizi; Othman, Siti Amira (Penerbit UTHM, 2020)
Nowadays, safety boots are necessary and essential to workers in order to avoid harm and injury at a workplace. Safety boots can be defined as a personal protective equipment (PPE) for foot protection at workplace from getting foot injuries caused by sharp object, hot object, splinters, and corrosive from chemical. Safety boots are further divided into 2 style which is formal and informal. The use of safety boots is mandatory in a work environment such as: • Handling hard and heavy object • Involve in handling round object that may dropped at your feet • Workplaces that are hazardous • Work that involved sharp object • Working with electric cable • Work on a floor with static electricity